Perlindungan Hukum Terhadap Korban Tindak Pidana Asusila Pada Media Sosial Dikaitkan Dengan Undang-Undang Informasi Transaksi Elektronik - Ghibran, Muhammad Zidane (Jurnal Ilmiah Wahana Pendidikan, 2024)
With the development of the era, technology is also developing rapidly. Technological developments make it easier for everyone to find what they need. The convenience of this technology has resulted in many people misusing technology to commit crimes or what is commonly called cybercrime. One of them is committing a crime of distributing immoral content electronically. Kendy is an electronic criminal who distributes naked photos of victims on social media. This study aims to find out what factors lead to the crime of transmitting electronic information that violates decency, and legal protection for victims of criminal acts of information and electronic transactions that violate decency based on Law Number 19 of 2016. The method used in this study using normative juridical. The results of this study are the factors that cause someone to commit immoral crimes, namely revenge, difficulty being detected by law enforcement officials, lack of experts, characteristics of the internet where people can walk around without an identity. Legal protection that can be given to immoral crimes on social media is based on article 45 paragraph 1 of Law No. 19 of 2016 which reads: "Any person who intentionally and without rights distributes and/or transmits and/or makes electronic information accessible and/or or Electronic Documents that contain content that violates decency as referred to in Article 27 paragraph (1) shall be subject to imprisonment for a maximum of 6 (six) years and/or a fine of a maximum of Rp. 1,000,000,000.00 (one billion rupiah)."